Inhibitory capabilities of ten medicinal plants used by traditional healers on mammalian carbohydrate digesting enzymes (alpha-amylase and alpha-glucosidase) - Ntini, ,V. P. (University of Limpopo (Turfloop Campus), 2013)
Diabetes mellitus is one of the fast growing chronic metabolic disorders throughout the world. It has become a life threatening disease and health burden. So far it can only be managed with commercial therapeutic agents, proper diet and exercise. People particularly from developing countries use medicinal plants to treat this condition. According to WHO, about 80% of the population in developing countries are dependable on medicinal plants. This prompted many researchers to explore the effectiveness and safety of these plants. In the current study ten medicinal plants were randomly chosen, screened for antidiabetic activity by testing their ability to inhibit α-amylase and α-glucosidase enzymes. The plants were tested using in vitro assays. The finely powdered leaves of each plant were extracted with hexane, chloroform, acetone and ethyl acetate. Phytoconstituents of each plant extracts were analyzed using both qualitative and quantitative methods. All plant extracts tested positive for phenols, flavonoids and all negative for starch. Their compounds were better separated in the TEA mobile system on the TLC plates. All plant extracts had more of total phenolics ranging between 0.1-400 GAE/mg than total flavonoids and condensed tannins. Antioxidant activity of the plant extracts was tested quantitatively at various concentrations using DPPH. Most plant extracts were able to scavenge the radicals produced by DPPH at highest concentration of 2.5 mg/mℓ. Not all plant extracts with the highest number of total phenolics had the highest antioxidant activity. For antidiabetic in vitro assays, plant extracts inhibited various percentages of both α-amylase and α-glucosidase activity at concentrations ranging between 0.019- 2.5 mg/mℓ. The best overall activity against both enzymes was observed in acetone and ethyl acetate plant extracts. Cassia abbreviata and Helinus integrifolius were even more active than acarbose which was used as positive control. These plant extracts inhibited both the enzymes in a dose dependent and non-competitive manner. Seeing that both extracts of C. abbreviata and H. integrifolius were consistent when inhibiting both enzymes, they were further evaluated for their effect on glucose uptake by the C2C12 muscle and H-II-4-E liver cells. All the plant extracts tested were able to increase glucose uptake in the muscle cells. However optimal increase was seen in the liver cells when treated with 250 µg/mℓ of acetone and ethyl acetate extracts of C. abbreviata. The cytotoxicity effects of both acetone and ethyl acetate of C. abbreviata and H. integrifolius was tested using the xCelligence system on RAW 264.7 cells. Different cell indexes were obtained after treating the cells with different concentrations (0.05,0.1 and 0.25 mg/mℓ) of each plant extracts respectively. The system was run for three days but the toxic effects of plant extracts were analyzed for the first ten hours. The results obtained shows that cell index decreased as the concentration of the plant extracts was increased. All the plant extracts were less toxic as compared to positive control, Actinomycin D. The leaves of H. integrifolius were further exhaustively extracted with hexane, dichloromethane, acetone, ethyl acetate and methanol respectively. Since the DCM extracts yielded the highest mass in quantity, it was further used for isolation of active compounds. Column chromatography and bioassay guided fraction led to isolation of a mixture of triterpenes identified as α and β-amyrin. The structure was elucidated using nuclear magnetic resonance technique. The inhibitory capability of the isolated compound against α-amylase enzyme was less than the crude extract which inhibited more than 50% of the activity at a concentration of 1 mg/mℓ.Based on the enzymes assays and cell culture work it can be concluded that C. abbreviata and H. integrifolius species are the best inhibitors of carbohydrate digesting enzymes, and therefore be used to manage postprandial hyperglycemia in the people with type 2 diabetes. However more work still need to be conducted for further isolation of more active compounds.
Thesis (M.Sc. (Biochemistry)) -- University of Limpopo, 2013
Keywords: Inhibitory capabilities; Medicinal plants; Traditional healers; Mamalian carbohydrates digesting enzymes; 616.462; Biochemistry; Glucosidase inhibitors; Traditional medicine -- South Africa; Diabetes -- Alternative treatment -- South Africa; Amylases -- Inhibitors